PERSEPSI PENGUNJUNG TERHADAP OBJEK WISATA LUBANG TAMBANG MBAH SOERO DI KOTA SAWAHLUNTO SUMATERA BARAT - Kurniawati, Ekasari; Achnes, Syofia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aims to get known the tourist perception of Mbah Soero Mine Hole in Sawahlunto West Sumatera. The research was done by taking samples are 100 respondents decided by slovin. Data analysis technique used is quantitative desciptive method to analyze the problems. Time research from December 2014 to Januari 2015. Data collection techniques took by observation, interview, questionnaire, and documentation. Data measurement technique was using likert scale to know the length of intervals.Based on the research results,that the tourist perception of Mbah Soero Mine Hole in Sawahlunto West Sumatera are cognitive aspect, affective aspect, and conatif aspect. For cognitive aspect about location tourist attraction is good. Affective aspect to be highest score about management tourist attraction of Mbah Soero Mine Hole in Sawahlunto. Such as the guide service,institusional of tourist attraction, tourist attraction facilities, and entrance ticket service are good. And conatif aspect about visitor come because Mbah Soero Mine Hole is heritage tourist attraction.The final result every aspect the tourist perception of Mbah Soero Mine Hole in Sawahlunto West Sumatera are goodKey Words: Tourist Perception, Tourism, Mbah Soero Mine hole ,Sawahlunto